HUBUNGAN WILAYAH KERJA TERHADAP KEJADIAN JAMUR PADA KARYAWAN PT.PERKEBUNAN NUSANTARA VII - Suryaningsih, Lely (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Dermatophytosis was a disease in tissues that contain substances on the horn for examplestratum corneum epidermidis, hair and nails caused by dermatophyte fungi group. Dermatophytosishad keratinofilik nature, each species of dermatophytes had an affinity for a particularhost. Zoophilic dermatophytes which primarily affects animals, and humans. This study aimed todetermine the relationship of the working area on the incidence of fungal infections of the employeesof PT. Plantation Nusantara VII in North Bengkulu. This research was observational analyticcross-sectional design, the independent variable was the area of employment, the dependentvariable was the incidence of fungal infections. The population was 29 employees PT. PerkebunanNusantara VII, samples of all employees PT.Perkebunan Nusantara VII with a total samplingtechnique. Data was analyzed using frequency distribution and bivariate using Chi-Squaretest. The results revealed that the majority of employees working in the processing of fungal infectionthat is equal to 88.2%, which was statistically significant relationship between the workingarea with the incidence of fungal infections. Director PT.Perkebunan Nusantara VII shouldpay more attention to the safety of its employees with a firmer giving rules and providing extensionignore the dangers of the use of personal protective equipment can cause fungal infections.